Colaboração científica na temática redes sociais: análise bibliométrica do ENANCIB no período 2009 - 2010 - Hilário, Carla Mara [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP] (My University, 2011)
The aim of this research is to point out the most productive researchers and institutions in the “Social Network” theme, in the ENANCIBs, from 2009 to 2010, as well as to describe their institutional scientific collaboration network. As research procedure, we searched for works with the entry network in the annuals of the event. 169 works were found, from which 120 were developed in co-authorship by 40 institutions. A matrix with the institutional coauthorships was created and the scientific collaboration network was reached. The results point out the same number of both most productive institutions and most productive authors. As for the scientific collaboration network, it is relevant that 37 institutions are interconnected by co-authorship. It’s also relevant that the studies in social network have been more and more present in the Information Science, mainly as investigative method for the construction of knowledge.

O objetivo desta pesquisa é evidenciar os pesquisadores e instituições mais produtivos na temática “Redes Sociais”, nos ENANCIBs, no período de 2009 a 2010 e descrever sua rede de colaboração cientifica institucional. Como procedimento de trabalho buscou-se, nos anais do evento, trabalhos com o termo redes, usado no contexto social. Foram localizados 169 trabalhos, com 120 desenvolvidos em coautoria por 40 instituições. Foi construída a matriz com as coautorias institucionais e gerada a rede de colaboração científica. Como resultado, observou-se o mesmo número de instituições e pesquisadores mais produtivos. Em relação à rede de colaboração científica, destaca-se que 37 instituições encontram-se interligadas por coautoria. Destaca-se, ainda, que os estudos em redes sociais têm se mostrado cada vez mais presentes na Ciência da Informação, particularmente como método investigativo para a construção do conhecimento.
Keywords: análise bibliométrica; Redes sociais; colaboração científica; Rede de coautorias